O recém nascido de extremo baixo peso. Estado aos 2-3 anos. Resultados do Registo Nacional de Muito Baixo Peso de 2005 e 2006 - Cunha, M (2013)
Background: Children born before 32 weeks or very low birth weight have a high risk for neurodevelopmental impairment. Aim: To analyze the condition of extreme low birth infants (weighing 1000g or less), born in the years 2005 and 2006, and included in the Portuguese National Very Low Birth Weight Network. Results: A total of 163 children were evaluated, 49.1% of which were males with a mean gestational age 27 weeks at birth, average birthweight 805.6 grams, and the average age at assessment 36 months. Children with birth weight under 25th percentile (p), were overweight (above p90) on the evaluation date. Moreover, children with birth weight higher than p50, on the evaluation date have had malnutrition (less than p5). Looking for sequels: four children (2.5%) had severe or profound deafness, three (1.9%) requiring hearing aids. One child was blind (0.9%) and 25 (17%) needed to wear glasses. Fifteen (9.7%) had cerebral palsy and thirteen (8.7%), neurological impairment (epilepsy, cerebral atrophy, microcephaly, hydrocephalus). We found development delay in 17 infants (10.6%). We considered 34 children (20.9%) as having some kind of neurodevelopmental impairment and 129 (79.1%) as normal. Special needs were found in 77 (49.7%) children, the most frequent being physical therapy in 39 (24.8%). Children with sequelae have had significantly higher need for any kind of support Conclusion: We do know now the neurodevelopment impairment and needs of this population as it is important in order to assess the quality of life of survivors, but also to identify strategies for diagnosing and intervention measures and support that these children will need.